2021
DOI: 10.1093/brain/awab321
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-phenotype correlations in SCN8A-related disorders reveal prognostic and therapeutic implications

Abstract: We report detailed functional analyses and genotype-phenotype correlations in 392 individuals carrying disease-causing variants in SCN8A, encoding the voltage-gated Na+ channel NaV1.6, with the aim of describing clinical phenotypes related to functional effects. Six different clinical subgroups could be identified: 1) Benign familial infantile epilepsy (BFIE) (n = 15, normal cognition, treatable seizures), 2) intermediate epilepsy (n = 33, mild ID, partially pharmaco-responsive), 3) developmental and epileptic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
126
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(135 citation statements)
references
References 52 publications
5
126
0
4
Order By: Relevance
“…Johannesen et al also recently reported two “likely pathogenic” in-frame SCN8A variants in a large cohort of Danish patients with SCN8A mutations ( Johannesen et al, 2021 ). The maternally inherited p.I888_V892delinsM variant was identified in one patient with moderate intellectual disability without epilepsy ( Johannesen et al, 2021 ).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Johannesen et al also recently reported two “likely pathogenic” in-frame SCN8A variants in a large cohort of Danish patients with SCN8A mutations ( Johannesen et al, 2021 ). The maternally inherited p.I888_V892delinsM variant was identified in one patient with moderate intellectual disability without epilepsy ( Johannesen et al, 2021 ).…”
Section: Discussionmentioning
confidence: 95%
“…Johannesen et al also recently reported two "likely pathogenic" in-frame SCN8A variants in a large cohort of Danish patients with SCN8A mutations (Johannesen et al, 2021). The maternally inherited p.I888_V892delinsM variant was identified in one patient with moderate intellectual disability without epilepsy (Johannesen et al, 2021). Another patient had a maternally inherited variant (E1774_A1777del) and presented with several types of seizures, including febrile, myoclonic, and atonic seizures, but normal intellect (Johannesen et al, 2021).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Na v 1.6 (encoded by SCN8A) is targeted by commonly used sodium channel blocking drugs that have been found to be the most efficacious ASMs for people with monogenic SCN8A- related epilepsies that are often due to channel gain-of-function. 48 Additional drugs targeting Na v 1.6 include safinamide and quinidine. RYR2 encodes a ryanodine receptor, is an established cardiac disorder gene, has recently been implicated in epilepsy 49,50 and is targeted by caffeine as well simvastatin, atorvastatin and carvedilol.…”
Section: Discussionmentioning
confidence: 99%
“…EEG generally shows a diffuse background with slow activities and focal epileptiform discharges, mainly in the posterior regions [48]. However, disease-causing variants of SCN8A have been recently related to rare cases of BFNE, increasing the number of genes associated with a wide range of epilepsy phenotypes [49,50].…”
Section: Genes and Pathogenic Variants Mostly Involved In Deesmentioning
confidence: 99%